Urban Infrastructure Resilience Assessment During Mega Sport Events Using a Multi-Criteria Approach - Serdar, Mohammad Zaher; Koc, Muammer; Al-Ghamdi, Sami G. (Frontiers in Sustainability, 2021)
Critical infrastructures share the same space and mutual dependencies, and consequently contribute to city’s overall resilience. However, each has different assessment methods and metrics, which prevents the integration of the performance results for different infrastructures into a single holistic evaluation index that can reflect the city’s overall resilience and expected performance. To address this challenge, we propose the development of a multi-criteria-based integration approach that can allow the combination of different evaluation results from different assessment methods through partial factors. The proposed equation incorporates several factors, which can be divided into four groups: 1) method-efficiency factors, 2) infrastructure importance factors, 3) infrastructures' interdependency factors, and 4) strict limits that ensure that the infrastructures are suitable for hosting mega sports events. Using this approach, we hope to open the way for future research into suitable factors and facilitate resilience-based design in sustainable development and municipal planning.